Occupational Health Safety and Physical Work Environment Conditions on Employee Performance - Sri Harini; Sudarijati; Muhamad Andri Yani (Indonesian Journal of Social Research (IJSR), 2019)
This study aims to determine the effect of occupational health safety programs and physical work conditions on the performance of production department employees at PT Bahagia Jaya Sejahtera. The population and sample amounted to 36 employees in the production section at PT Bahagia Jaya Sejahtera. Data collection through questionnaires and interviews. Instrument testing is done with validity and reliability. Analysis of research data includes multiple regression analysis, correlation and simultaneous and partial significance tests. Based on the results of multiple regression analysis the occupational health safety program and physical work environment conditions have a positive and significant effect on performance and the F test results state that simultaneous occupational health safety programs and physical work environment conditions affect employee performance. While the results of the test state that workload and work environment partially affect employee performance Increased workload within the limits of the ability of employees can improve employee performance.